Análise dialélica e inter-relação entre caracteres em cultivares de melancia forrageira - Santos, Roberta Machado (2016)
This study aims to identify promising progenitors and hybrids for crop improvement of the forage watermelon, for this purpose the heterosis, general and specific combination capacities were estimated, in addition, the phenotypic correlation, the path analysis between morphoagronomic and bromatological characteristics were determined. Five progenitors were evaluated; LPG (1), VM (2), MR (3), BGCIA 228 (4) and Jojoba (5) belonging to Embrapa Semiárido’s BAG, the ten F1’s were obtained from balanced diallel crossing. An augmented design in complete randomized blocks, with tree replications and eight plants per plot was used. The following characteristics were evaluated: FRP, FRN, PP, FRC/DT, CES, PES, TSS, NS, P100S, PFS, PSS, ProdF, CP, NDF, IVDMD, EE and K. Among the genotypes, potentiality for exploitation in crop improvement programs was observed. The choice of elongated fruit took into account the preference of agriculturists, resulting in the selection of all progenitors expressing this feature. The hybrids were obtained and evaluated in order to select the most promising for obtaining superior progenies to their genitors for the evaluated characteristics. Regarding the production, hybrids 1x4 and 4x5 stood out in obtaining more prolific progenies. The heterosis for bromatological characteristics was low, except for K. The general combining ability indicated the potential of the progenitor VM in obtaining progenies with higher CP and EE levels, as well as MR can contribute to increase fruit production. From the specific combining ability, it was verified that the hybrid 1x4 mostly showed FRP, NS, PSS and EE, as the hybrids 2x4, 3x4 and 3x5 displayed FRN, IVDMD and CP, respectively. From the phenotypic correlation, it was observed that the fruit with enhanced FRC/DT will possess greater PES and FRP, however less CP. The ridge path analysis, with PP dependent variable showed positive and low direct effects to the majority of the characteristics, moreover, indicated the reduction in the CP and NDF contents, important characteristics to the forage plants. The path analysis showed that the EE may be used in the selection of progenitors with higher PB levels. This work provides the first information on the pre-improvement of this culture, contributing to the achievement of more productive progenies and composed of higher levels of EE and CP, important elements for increased animal productivity.